Intraoperatively Diagnosed Cerebellopontine Angle Facial Nerve Schwannoma: How To Deal With It. (September 2014) - Bacciu, Andrea; Medina, Marimar; Ben Ammar, Mehdi; D'Orazio, Flavia; Di Lella, Filippo; Russo, Alessandra; Magnan, Jacques; Sanna, Mario
Objective: This study aimed to report our experience in the management of patients with intraoperatively diagnosed intracranial facial nerve schwannomas (FNSs) and propose a decision-making strategy. Methods: Twenty-three patients with FNS of the internal auditory canal and/or cerebellopontine angle operated on between 1992 and 2012 were identified. Results: Preoperatively, all cases have been radiographically diagnosed as vestibular schwannomas. Operative procedures consisted of total tumor resection with grafting in 43.4% of patients, near-total resection leaving behind the tumor capsule overlying the facial nerve in 21.7%, total tumor resection with preservation of anatomic continuity of the facial nerve in 13%, and subtotal resection in 4.3%. Four patients (17.4%) underwent bony decompression with no tumor removal. Conclusion: Management of FNS diagnosed at surgery represents a significant clinical challenge. We considered total tumor resection with grafting when patients presented with preoperative facial nerve palsy (≥ grade III). Both subtotal and near-total tumor removal can be performed in patients with preoperative good facial function and/or large tumors with brainstem compression. Patients with small tumors who were selected for hearing preservation surgery can be considered for bony decompression. Fascicle preservation surgery may be an option when a clear cleavage plane between the tumor and the facial nerve is found.